Homoafetivity in portuguese literature : the case of the novel o barão de lavos - Monteiro de Melo Neto, Moses (Seven Editora, 2023)
In this study, we are going to deal with homosexual relationships between men, especially how they are represented in literature and, in a more specific way, in the Portuguese naturalist novel O Barão de Lavos. What is the opposite-sex or same-sex preference? A genetic predisposition or upbringing? A combination of both? The fact is that many, all over the world, continue to have same-sex relationships, and nothing can stop the feelings and practices of such a relationship, mainly because in some there is not even sex. But is there a genetic predisposition to homosexual attraction? Now, sexual behavior in the attraction of the opposite sex has been 'normalized' throughout history, however, the predisposition of homosexual desire was, historically, considered abnormal or, let's say, unnatural.            DOI: 10.56238/pacfdnsv1-100